The influence of molecular structure of fatty acid monoalkyl esters on diesel combustion - Schönborn, Alessandro; Ladommatos, Nicos; Williams, John; Allan, Robert; Rogerson, John (Combustion and flame, 2009)
The subject of this paper is a series of experiments conducted on a single-cylinder research engine investigating the influence of molecular structure on the combustion behaviour of fatty acid alcohol ester (biodiesel) molecules under diesel engine conditions. The fuels employed in these experiments comprised various samples of pure individual fatty acid alcohol ester molecules of different structure, as well as several mixtures of such molecules. The latter consisted in biodiesel fuels produced by the transesterification of naturally occurring plant oils or animal fat with a monohydric alcohol. It was observed that the molecular structure of the fuel significantly influenced the formation of NO x and particulate matter and their respective concentration in the exhaust gas. The influence on the formation of NO x in particular, appeared to be exerted first through the effect which the molecular structure had on the auto-ignition delay occurring after the fuel was injected into the combustion chamber, and second through the flame temperature at which the various molecules burned. The emission of particulates on the other hand showed correlation with the number of double bonds in the fuel molecules for the case of larger accumulation mode particles, and with the boiling point of the fuel samples for the case of the smaller, nucleation mode particles. The effect of ignition delay on the exhaust emissions of these pollutants was isolated by adding the ignition promoting molecule 2-ethylhexyl nitrate to some of the fuel samples in closely specified concentrations, so as to equalise the ignition delay for the relevant fuel samples. The removal of the ignition delay as a main influence on the combustion process enabled the observation of the lesser effects of adiabatic flame temperature.